A single center experience with the newly designed R stent in small coronary vessels - Ilkay, Erdo?an; Karaca, Ilgin; Karadaban, Arif; Kiliço?lu, Ali Erhan; Yalniz, Mehmet; Ozbay, Yilmaz; Arslan, Nadi (My University, 2001)
BACKGROUND: Over the past 10 years stents have been used more frequently for the treatment of de novo coronary artery stenosis. Initally these devices were used primarily in coronary arteries with diameters ranging from 3.0 to 4.0 mm. Traditionally, coronary arteries less than 3.0 mm in diameter were treated with only balloon angioplasty, due to the unavailablity of flexible, low profile, small diameter stents. In the past three years, many stents have been designed to be implanted in small coronary arteries. OBJECTIVE: The objective of this study was to evaluate the safety and feasiblity of the R Stent in patients with coronary lesions located in coronary arteries with a reference diameter 2.5-3.0 mm. METHODS AND RESULTS: Between November 1998 and September 1999, 32 patients with stable (37%) and unstable (63%) angina treated with the R Stent were included in this study. The treated lesions were in the right coronary artery (RCA) (n = 13), left cirumflex coronary artery (LCX) (n = 10), and left antedor anterior descending coronary artery (LAD) (n=9),. Of these lesions thirteen were anatomically complex. Stent deployment was successful in 97% with one crossing failure in a patient with a vessel tortuosity of greater than 75 degrees of the circumflex artery. No post-procedual major adverse cardiac and cerebrovascular event (MACCE) occurred within 30 days of stent implantation. After the procedure, patients were scheduled for a two-week telephone follow-up and a one-month clinical evaluation. At 30 days, only one patient (3%) experienced the recurrence of angina Canadian cardiovascular society classification ((CCS) Class 2). All other patients were event and angina free. CONCLUSION: This first clinical experience in patients with small vessel disease shows that the use of the R stent is safe and feasible with low rates of acute stent thrombosis.
Keywords: Angioplasty; Coronary disease; R Stent; Small diameter stent